From the dark end of the street to the bright side of the road? investigating the returns to residential mobility in Britain - René Böheim; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2000)
We examine the impact of moving home, the distance moved and reasons for moving on both household income and labour market earnings for a representative sample of individuals using panel data. Our results suggest that there are monetary returns to migration which apply to both household income and labour market earnings. However, not all migrants enjoy these returns, which depend on distance moved, family structure, and the employment situation of other family members. Further, returns to migration may not be enjoyed for some time after the move, emphasising the need for panel data in studies of residential mobility. Using data that are too recent relative to the time of migration will yield misleading results and underestimate the size of the premium attributable to residential mobility.
Keywords: 330